Pengaruh Tangibility, Firm Size, Gender Diversity, Dan Growth Terhadap Capital Structure - Elbert Christian, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This research has a purpose, to improve the effect of tangibility, firm size, gender diversity, and growth to capital structure on manufacture company that listed on Indonesia stock exchange during the year 2016-2018 with 69 sample.the model tahat use in this research was fixed effect model, common effect, and random effect model. The result of the research was tangibility has negative effect on capital structure, firm size has negative effect on capital structure, gender diversity and growth has no significant effect on capital structure.Keywords: Firm Value, Capital Structure, Liquidity and Dividend Policy.